Complete mitochondrial genomes of three sea basses Lateolabrax (Perciformes, Lateolabracidae) species: Genome description and phylogenetic considerations. (August 2016) - Shan, Binbin; Song, Na; Han, Zhiqiang; Wang, Jun; Gao, Tianxiang; Yokogawa, Koji
Abstract: Genus Lateolabrax consists of three species, Japanese sea bass Lateolabrax japonicus, spotted sea bass Lateolabrax maculatus and blackfin sea bass Lateolabrax latus . The complete mitochondrial DNA (mtDNA) of the three sea basses were amplified and sequenced to characterize and discuss their phylogenetic relationships. The length of mitogenomes was 16, 593 bp, 16, 479 bp and 16, 600 bp, respectively, and all of them consisted of 13 protein-coding genes, 2 ribosomal RNA (rRNA), 22 transfer RNA (tRNA) and a control region, which are typical for mtDNA of vertebrate. Most genes were encoded on the H-strand, except for the ND6 and eight tRNA genes encoding on the L-strand. A significant variation among the three species was detected in length of the control region. Phylogenetic relationship among the three species was constructed based on the datasets, including the 12 protein-coding genes (except ND6 gene), 22 tRNA and 2 rRNA sequences. The results supported the sister taxon between L . japonicus and L . maculatus . The genetic resources reported here are useful for further studies in taxonomy and phylogeny of the three sea basses and related species. Graphical abstract: Highlights: Mitogenome comparison. Divergence of Lateolabrax mitogenomes. Mitogenomic phylogeny.